Isolamento sonoro aéreo de partições verticais em habitações multifamiliares em Maceió-AL - Penedo, Rafaella Cristina Teixeira (2014)
The NBR 15575 (ABNT, 2013) called “Performance Standard – Dwellings” sets out mandatory minimum requirements for the various elements of construction in favour of the performance of buildings, used as benchmark for builders and buyers in the analysis and quality assurance of their homes. This standard, in force since July 2013, together with the parameters and methods of international standards, is the basis for the evaluation work of the acoustic performance of houses in Brazil. Future diagnosis based on this standard will serve to support initiatives suitability of new ventures regulatory requirements. Manufacturers of construction systems should also tailor their products and disseminate the results of the performance tests, which assist the designer in the specification of the components of the buildings, providing sufficient choice of materials with better performance data. The aim of this study is to evaluate the soundproofing airborne noise of vertical partitions in apartments in Maceió-AL, presenting an adaptation of certification of acoustic performance. As evaluation method, we selected two apartments in separate buildings of two construction companies with different configurations of plants and building systems where Field measurements were carried out to know the degree of sound insulation of facades of bedrooms and internal partitions environments that make up the housing units under study. With the results, we found that the acoustic insulation of the objects under study were not satisfactory, as the results for the airborne noise, mostly were bellow the minimum levels required by the performance standard NBR 15575 (ABNT, 2013). It is evident, therefore, a need, not just assessment and control of noise performance, but also of major concern to design strategies and constructive interventions that provide users with appropriate conditions of comfort and privacy.